Flue Gas Emissions from the Burning of Asphaltite and Lignite in a Rotating Head Combustor with Secondary Air Delivery - Oner, Cengiz; Altun, Sehmus (Amer Chemical Soc, 2014)
In this work, a rotating head combustor, which has been designed for burning the coking coals effectively, was deployed to burn a range of coals available in Turkey under agitation conditions with secondary air delivery. The coals were lignite (Tuncbilek, Turkey) and asphaltite with high swelling property known as coking coal (Sirnak, Turkey). The performance was investigated by determining the temperature distribution on the head, combustion efficiency, and the amount of unburned substances (such as C) in the ash, and flue gas emissions of O-2, CO, CO2, SO2, and NOx were measured during the experiments. The effect of operating conditions such as excess air ratio (EAR) and coal feeding rate was also investigated. The temperature distribution on the head was found to be high in the case of using the secondary air delivery and combustion efficiency was above 80% at the EAR of 1.3 and coal feeding rate of 9 kg/h when asphaltite was used as the fuel in the rotating head combustor. The comparison between asphaltite and lignite could lead to the conclusion that asphaltite provides slightly higher efficiency than lignite, and the difference is very small at the EAR of 1.3. When flue gas emissions are compared, it is seen that CO and SO2 emissions from asphaltite combustion are higher while CO2 and NOx emissions are lower than those derived from lignite combustion. For the combustion of both fuels, secondary air sent to the bed surface had a noticeable influence on combustion and emission characteristics via its effect on the combustion of volatility products and released gases from the bed surface. However, it should be more for lignite combustion in order to get better performance.
4th International Conference on Biorefinery-Toward Bioenergy -- DEC 03-05, 2013 -- Xiamen, PEOPLES R CHINA
Keywords: Circulating Fluidized-Bed; Coal; Carbon